Quality Testing of Order Management Information System Based on Mccall’s Quality Factors - Rahmawati, Feri; Musyafa, Muhammad Akid; Fauzi, Muhammad Dzulfikar; Mulyanto, Agus (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2016)
Satoedjari Merch is one of the companies that utilize convection system in managing information as a support order. After implementing a management information system, the necessary attention is to the quality of the system so that it can scale very well and as needed. Order Management System in Satoedjari Merch is still in the early stages of use, it requires quality testing system to maximize its benefit. One of good software quality is if it meets those aspects of McCall's Quality Factor. This study uses Product Operation aspect, because this aspect tests the quality related with system activity when the system is used. In the aspect of product operations, there are five factors that is correctness, reliability, efficiency, integrity and usability. According to the test results, it is known that the Order Management Information Systems of Satoedjari Merch for operator system excellent quality are the truth factor, reliability, convenience and efficient. Factors that have low values are on the relationship system and data security.